2010
DOI: 10.1155/2010/862569
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fecal Content of Fatty Acids and Cyclooxygenase mRNA Expression and Fatty Acid Composition in Duodenal Biopsies, Serum Lipoproteins, and Dietary Fat in Colectomized Familial Adenomatous Polyposis Patients

Abstract: A few familial adenomatous polyposis studies have focused upon faecal sterols and bile acids but none has analysed the fecal content of fatty acids. We report here findings of an observational study on 29 colectomized familial adenomatous polyposis patients that describe the fecal content of fatty acids, and relate this to the proportions of fatty acids and levels of cyclooxygenase mRNA expression in duodenal biopsies, levels of serum lipoproteins, and diet. In the ileostomy group separately (n = 12), the feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…1 and 2). 1 Antibodies against ␣-gustducin (sc-395) (35,51), GLP-1 (sc-7782) (35), and GIP (sc-23554) (24,95) have been validated previously in the above-mentioned papers from our laboratory and/or from others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). 1 Antibodies against ␣-gustducin (sc-395) (35,51), GLP-1 (sc-7782) (35), and GIP (sc-23554) (24,95) have been validated previously in the above-mentioned papers from our laboratory and/or from others.…”
Section: Methodsmentioning
confidence: 99%
“…The lumen of the colon lacks dietary sugars, but is filled with microbiota, nondigestible matter, and fermentation products, such as short-chain fatty acids (SCFAs), ammonia, phenols, amines, and bile acids (12,23,50,84). Medium-and long-chain fatty acids (LCFAs) are also detected in fecal content from patients with small bowel resection on a high-fat diet (36) and from colectomized patients (1). Interestingly, the SCFA receptor G protein-coupled receptor (GPR) 43 (6, 47) is coexpressed with GLP-1 in both human and rat colon L cells (37).…”
mentioning
confidence: 99%
“…Concentrations of fecal LCFAs are related to various factors, such as dietary intake, gastrointestinal digestion and absorption of lipids, bile secretion, FA-binding proteins, FA transport protein, and small intestinal transit time, among others [30]. Some specific FAs have been linked to inflammatory activity [31][32][33], making the composition of fecal FAs a potential indicator for gastrointestinal health. In our study, we found increased fecal concentrations of 9 out of 12 targeted LCFAs in cats with CE; these increases might have resulted from maldigestion, malabsorption, inflammation, dysbiosis, and abnormal lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%